Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1103/physrevlett.91.066403
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Jahn-Teller Distortions at the Antiferromagnetic Transition inLaTiO3

Abstract: LaTiO3 is known as a Mott insulator which orders antiferromagnetically at T(N)=146 K. We report on results of thermal expansion and temperature dependent x-ray diffraction together with measurements of the heat capacity, electrical transport measurements, and optical spectroscopy in untwinned single crystals. At T(N) significant structural changes appear, which are volume conserving. Concomitant anomalies are also observed in the dc resistivity, in bulk modulus, and optical reflectivity spectra. We interpret t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
67
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(72 citation statements)
references
References 32 publications
5
67
0
Order By: Relevance
“…In particular, we note that LaTiO 3 showed a structural transition at its magnetic transition temperature. Structural studies using x-ray and neutron diffraction techniques indicated a structural transition near the magnetic transition temperature, 22,23 and an optical study on LaTiO 3 showed that the additional phonon modes appeared below the magnetic transition temperature due to the structural transition. 19 However, the electronic structure and Mott gap of LaTiO 3 hardly changed with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, we note that LaTiO 3 showed a structural transition at its magnetic transition temperature. Structural studies using x-ray and neutron diffraction techniques indicated a structural transition near the magnetic transition temperature, 22,23 and an optical study on LaTiO 3 showed that the additional phonon modes appeared below the magnetic transition temperature due to the structural transition. 19 However, the electronic structure and Mott gap of LaTiO 3 hardly changed with temperature.…”
Section: Resultsmentioning
confidence: 99%
“…, where large background and Fano shape of the phonon line near 300 cm −1 have been observed, may also indicate orbital fluctuations coupled to lattice vibrations. Some recent experimental results on the temperature dependence near T N of neutron and x-ray diffraction, heat capacity and infrared spectra [4,5], however, provide evidence for noticeable deformation of TiO 6 octahedra and structural anomaly near the antiferromagnetic ordering, which indirectly supports the concept of orbital ordering.The observation in the Raman spectrum of insulating rare earth titanates of structureless background and Fano interference is highly unusual. At the same time, it is well known that transport and magnetic properties of LaTiO 3 [7,8,9] depend crucially on sample's stoichiometry.…”
mentioning
confidence: 92%
“…Pavarini et al 23 argue that the values of the tilting and the concomitant shift of the RE sites would determine the splitting of the orbital levels 23 . However, the lattice parameters and the octahedron deformation in LaTiO 3 exhibit clear anomalies around the magnetic ordering suggesting that there is an intrinsic coupling between orbital degrees of freedom and the crystal structure 5,35 . It is the aim of the present work to further elucidate this orbital-lattice coupling in the RETiO 3 series and to separate the intrinsically electronic effects from tilt and rotation distortions.…”
Section: Introductionmentioning
confidence: 99%